INCIDENCE OF MALARIA/TYPHOID CO-INFECTION AMONG ADULT POPULATION IN UNWANA COMMUNITY, AFIKPO NORTH LOCAL GOVERNMENT AREA, EBONYI STATE, SOUTHEASTERN NIGERIA - Odikamnoro, O.O.; Ikeh, I.M.; Okoh, F.N.; Ebiriekwe, S.C.; Nnadozie, I.A.; Nkwuda, J.O.; Asobie, G.C. (African Journal of Infectious Diseases (AJID), 2017)
Background: Malaria and typhoid fever are two leading infections of poverty with serious health and socioeconomic impacts, and due to their geographical overlap, co-infections are very common. Their mimicking symptomatology often present with gross misdiagnosis and mistreatment. This study was carried out to determine the incidence of malaria and typhoid co-infections among adult population in Unwana Community, Afikpo-North Local Government Area of Ebonyi State.Materials and Methods: Three hundred and fifty (350) individuals were examined, their blood samples subjected to microscopic examination and widal agglutination tests, for identification of Plasmodium parasites and antibodies to Salmonella enterica serovar typhi respectively. Questionnaire was administered to obtain information on malaria/typhoid management practices.Results: Out of the 350 blood samples analysed, 190 (54.2%) were positive for malaria, 173 (49.4%) were positive for Salmonella enterica serovar typhi, while 127(36.2%) were positive for both typhoid and malaria. However, prevalence of malaria parasite was statistically significant in relation to sex (p<0.05), as males had 50% prevalence and females, 58%. For Salmonella enterica serovar typhi, the prevalence was not statistically significant in relation to sex (p>0.05); while males had 57% prevalence for Salmonella enteric serovar typhi, females had 42%. Sex was statistically significant (p<0.05) concerning prevalence rate of malaria/typhoid co-infection; males had 35% co-infection rate while females had 37%. The management practices studied revealed that over 80% of the respondents preferred environmental sanitation as the best prevention/control method. In the case of treatment, buying medicine from pharmacy shops was common (48%). This was followed by the use of herbal remedies (31%), while appreciable number adopted self-treatment method (18%).Conclusion: Both malaria and typhoid were prevalent among the studied population with high rate of co-infection. Co-infection was higher in females than males and use of herbal medicine for treatment was common. Efforts should be made to improve on the living conditions of the people of Unwana and also, there should be public enlightenment on the preventive and control measures of the two diseases. Since both diseases have similar symptomatology, treatment should be based on adequate laboratory diagnosis. Also, personal hygiene is hereby encouraged among the populace.